2006
DOI: 10.1207/s15327663jcp1601_7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Culture, Gender, and Moral Obligations on Responses to Charity Advertising Across Masculine and Feminine Cultures

Abstract: Two studies investigated the effects of charity advertising on perceptions of moral obligation to help others and gauged ad evaluation. This was done in cultures that were similar in individualism but differed in either masculinity (United States and Canada) or femininity (Denmark and Norway). Participants read appeals that solicited donations to charity by focusing on either egoistic or altruistic motives. In masculine cultures, men preferred the egoistic ad and women preferred the altruistic one. In feminine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 42 publications
7
98
1
2
Order By: Relevance
“…Women proved to be more careoriented than men, who were more justice-oriented. These gender adaptation effects were corroborated in three follow-up studies (Brunel and Nelson, 2003, Study 2;Nelson et al, 2006, Study 1, Americans;Nelson et al, 2006, Study 2, Canadians), but not in Brunel and Nelson (2003, Study 1) 1 . In sum, the research evidence to date does not indicate that one of the fundraising appeals systematically outperforms the other, but rather that their effectiveness may depend on the audience's gender.…”
Section: Help-others and Help-self Appeals Adapted To Gendered Valuesmentioning
confidence: 85%
See 2 more Smart Citations
“…Women proved to be more careoriented than men, who were more justice-oriented. These gender adaptation effects were corroborated in three follow-up studies (Brunel and Nelson, 2003, Study 2;Nelson et al, 2006, Study 1, Americans;Nelson et al, 2006, Study 2, Canadians), but not in Brunel and Nelson (2003, Study 1) 1 . In sum, the research evidence to date does not indicate that one of the fundraising appeals systematically outperforms the other, but rather that their effectiveness may depend on the audience's gender.…”
Section: Help-others and Help-self Appeals Adapted To Gendered Valuesmentioning
confidence: 85%
“…Contrary to expectations expressed above, women from the feminine, Danish culture (Study 1) and the feminine, Norwegian culture (Study 2) were more persuaded by the help-self appeal than by the help-others appeal. Nelson et al (2006) suggest that overlapping gender roles in these highly feminine cultures make women relatively more masculine than men, but this does not seem consistent with Hofstede's (1980Hofstede's ( , 2001 empirical data relating to masculinity-femininity. The overlap between gender roles has indeed been claimed and demonstrated in feminine cultures, but in such a way that both men and women take on relatively feminine roles.…”
Section: Help-others and Help-self Appeals Adapted To Cultural Valuesmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, they may be less motivated to correct for the presumed bias as value-laden advertising may signal to consumers how much importance their society attaches to these values. After all, given that ads are more persuasive when they appeal to the values of the audience (Nelson et al 2006;Van Baaren and Ruivenkamp 2007), it makes sense that advertisers make use of values that are shared by as many consumers as possible. In sum, consumers who view advertising as informative may be less motivated to reduce the possible bias and therefore assimilate to the 'advertised' values.…”
Section: Advertising As a Situational Cuementioning
confidence: 99%
“…For instance, Davis and Knowles (1999) showed that small changes in a request script can produce big differences in compliance with the request. Research on advertising appeals aimed at gaining contributions to charity has shown that message elements such as pictures (Perrine, 2000), guilt appeals (Hibbert, Smith, & Davies, 2007), as well as focusing on egoistic and altruistic motives (Nelson, Brunel, Supphellen, & Manchande, 2006) can increase the effectiveness of these appeals. In sum, previous research highlighted either the characteristics of the donators or the features of the charity messages in explaining charitable behavior.…”
Section: Discussionmentioning
confidence: 99%